Widerstand und Verfolgung in Essen 1933 - 1945 - Steinberg, Hans-Josef; Schröter, Hermann; Streich, Gustav; Peukert, Detlev; Schmidt, Ernst; Boll, Ilka; Vogt, Paul
Bemerkungen: Archivstempel auf der rechten unteren Ecke